Species composition of malarial mosquitoes Kharkiv region. Natural factors of malaria transmission - Gazzawi - Rogozinа, L (Annals of Mechnikov's Institute, 2020)
Introduction. This article describes the species composition of the dominant Anopheles mosquitoes in the Kharkiv region, the season of their possible effective infection, as well as ongoing anti-malaria activities . Key words: malaria , mosquitoes, p . Anopheles, epidemiology, census, hydraulic events. Material & methods. The analysis of entomological and meteorological situation in Ukraine and in the Kharkiv region according to data of the Ukrainian Center of control and monitoring of diseases of the Ministry of Health of Ukraine and Kharkiv regional laboratory center. Collection of material (imaginal and larval) was carried out on the territory of natural and artificial water bodies of Kharkiv region in the period 2013 - 2014. When collecting the material used conventional accounting methods mosquito populations. On the territory of the region under study, we have found 30 species of mosquitoes three genera: Anopheles, Culex, Aedes. Results & discussion. Epidemiological role of each species of mosquitoes depends on several conditions. Dangerous vector species can only be found in large numbers, a significant percentage of individuals in a population that feeds on the blood of man, having a sufficiently long season activity and a sufficient number of females surviving to age possible maturation of sporozoites in their body. In Ukraine, the major carriers - Anopheles maculipennis, An. m. messeae, An. m. atroparvus, An. claviger, An. plumbeus, An. hyrcanus. Mosquito species registered in the territory of the Kharkiv region are susceptible to currently known types of human malaria parasites . Moreover, the dominant species in terms of urban landscapes are An.maculipennis and An.messeae . These species possess all the qualities necessary to be considered dangerous malaria vector control. They are well infected with the three main types of human parasites. In the study area , in terms of urban landscapes, gonoaktivnye females occurs within 3.5-4 months, and Preimaginal stages in reservoirs - about 4.5 months. The maximum number of species observed in mid-July. Due to the high number of attacks and activity in the summer , as well as the confinement of breeding sites to human settlements , An.maculipennis, An. messeae pose the greatest epidemiological risk. Conclusion. All of the above demonstrates the improvement of environmental conditions for the spread of malaria : growth of the transporter , the increase in precipitation , temperature longer transmission period of invasion .